Criteria for effective regional scale catchment to reef management: A case study of Australia's Great Barrier Reef. (December 2021) - Creighton, Colin; Waterhouse, Jane; Day, Jon C.; Brodie, Jon
Abstract: Many coastal and marine ecosystems around the world are under increasing threat from a range of anthropogenic influences. The management of these threats continues to present ongoing challenges, with many ecosystems increasingly requiring active restoration to support or re-establish the ecosystem's biological, cultural, social and economic values. The current condition of Australia's Great Barrier Reef (GBR) and its threats, including water quality, climate change and the loss of wetlands, causing the continuing decline in the GBR's ecological condition and function, has received global attention. Activities aimed at halting these declines and system restoration have been underway for over forty years. These activities are challenging to implement, and much has been learnt from their various outcomes. This paper considers the GBR and the associated management activities as a case study for regional scale catchment to reef management. It summarises the management approaches to date, describing the key role that science, policy and community have played in underpinning various investments. Four criteria for success are proposed: the lead role of the community, the need for a systems approach, the need for targeted, cost-effective and sustainable long-term investment, and importantly, building knowledge and maintaining consensus and political commitment. Highlights: Activities have intended to halt the decline and restore values of the GBR for decades. The history of GBR catchment to reef provides a foundation for learning. Criteria for success are identified to improve the condition and resilience of the GBR. Integrated socio-ecological approaches will facilitate successful management. Community leadership, long-term commitment and a solid knowledge base are essential.